ARTIKEL PENDAMPINGAN PENJAMINAN DAN PENGENDALIAN MUTU PENDIDIKAN MASYARAKAT DI PKBM BINTANG HARAPAN KOTA BANDUNG - mutia raihani (UNIVERSITAS NEGERI MAKASSAR, 2023)
Non-formal education has an important role in meeting the needs of society in the field of education, especially in improving human resources in facing global competition which is increasingly real and felt by society. To face these challenges, of course, we can all understand that non-formal education units have a big role in serving people who do not have the opportunity to obtain education services through formal channels. So that education services to the community can be guaranteed, one of the government's efforts is to carry out a program to improve the quality of non-formal education. Among them is institutional quality assurance in the form of fulfilling 8 (eight) national education standards consisting of Graduate Competency Standards, Content Standards, Process Standards, Educator and Education Personnel Standards, Management Standards, Infrastructure Standards, Financing Standards and Education Assessment Standards. The type of research that was carried out was a comparative study in fulfilling the 8 (eight) standards, we have done it on PKBM Bintang Harapan which has a â€œBâ€ accreditation.Keywords: Non-formal Education, National Education Standards.